Mycological Indoor Air Quality Assessment of Ultra-Modern Market Grains’ Grinding Mills in Dutse, Northwest Nigeria - Adeleye Adeniyi Olarewaju; Abdullahi Ibrahim; Bate Garba Barde Barde; Amoo Florence Kemi; Asaju Catherine Iyabo; Yerima Mohammed Bello (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
This research aimed to assess the mycological indoor air quality of the grains’ grinding mills situated in the Dutse ultra-modern market. A simple random sampling method was employed to select nine (9) shops where grains are milled. Settle plate method through the use of fifty-four (54) sterile sabouraud dextrose agar (SDA) plates was adopted for fungal isolation in the morning, afternoon and evening. Fungal isolates were subsequently identified using standardized methods. Results obtained indicate that depending on the sampling period and operation status of the grinding mills, all the sampling points examined were heavily contaminated with total mean fungal load in the morning (4084 CFU/m3), evening (3867 CFU/m3), and afternoon (3818 CFU/m3). However, the mean fungal load obtained in the morning from shop C (6426 CFU/m3) was significantly different from other shops (p< 0.05) while the mean fungal loads obtained across all the shops in the afternoon and evening were not significantly different from each other (p> 0.005). Mucor plambeaus (22.22%), Aspergillus flavus (16.67%), Aspergillus niger (20.37%), Fusarium spp. (22.22%) and Penicillium spp. (18.52%) were isolated across the grinding mills. Results obtained indicate that depending on the time of the day and operation status of the grinding mills, the studied indoor environment allowed fungal aerosols to build up which could serve as a potential reservoir of fungal infections. It is therefore recommended that safety measures should be adopted with a view to reducing fungal pollution at the grains’ grinding mills.